Pengaruh Kepemimpinan Kepala Sekolah, Lingkungan Kerja dan Beban Kerja Terhadap Kinerja Guru Sekolah Menengah Kejuruan Swasta di Kota Semarang - Harjuna Ardi Nugraha Patria Pinandita; Sri Sudarsi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the impact of school leadership, work environment, and workload on teacher performance. The object of this research is a private vocational high school in Semarang City. The results show that the independent variables of school leadership and work environment have a positive and significant effect on teacher performance, while the independent variable of workload has a negative and insignificant effect on teacher performance. Good school leadership in providing guidance, support, and motivation to teachers will influence the improvement of teacher quality and work productivity. A good work environment with adequate facilities and a supportive atmosphere will help teachers work more effectively, increase motivation, and ultimately improve teacher performance. Heavy workloads can lead to physical and mental fatigue, which can ultimately disrupt work productivity and performance quality. An imbalanced workload can cause stress, decreased motivation, and exhaustion, leading to a decline in teacher performance.